Accounting ethics and the fragmentation of value - Baud, Celine (Journal of business ethics, 2021)
This study investigates how one important accounting professional authority - CPA Canada - discusses accounting ethics and exhorts its members to think about ethics-related issues. To do this, we rely on empirical evidence of the types of arguments used by CPA Canada to describe what they consider acceptable moral justifications in a variety of practical situations that accountants may encounter. We argue that the articles contained in the profession’s primary publication for all members, CPA Magazine, offer a wealth of such evidence. We analyze 237 articles about accounting ethics that were published in CPA Magazine from January 2000 to December 2017, and find evidence of moral pluralism (Nagel in Mortal questions. Cambridge University Press, Cambridge, 1979). Six categories of justifications dominate: private commitments, utility, perfectionist ends, general duties, and specific obligations, plus self-interest. Of these categories, the specific obligations logic is the most widely used. We offer a tentative explanation, and discuss the implications of our findings for a better grasp of the complexities of accountants’ practical conflicts and a rethink of the ongoing tension between professionalism and commercialism.